Penyuluhan dan Pemberian Obat Cacing Tingkat TK di RA Muslimat NU Tarbiyatul Athfal - Heni Setyoningsih; Miranti Amalia; Siti Safuroh; Gendis Purno Yudanti; Dwi Susiloningrum; Hasty Martha Wijaya; Dian Arsanti Palupi (Jurnal Surya Masyarakat, 2024)
Worms are still a health problem in Indonesian with a general prevalence that is still very high, varying between 2.5% - 62%. These worms can result in decreased health, nutrition, intelligence and productivity. Worms cause loss of carbohydrates and protein as well as blood loss, thereby reducing the quality of human resources. One way to control worms is by giving mass medication to prevent worms in vulnerable groups to stop the spread of worm eggs from suffers to the surrounding environment, in which case the drug albendazole is given. The method used to overcome this problem is by providing counselling and administering the drug albendazole at the RA Muslimat NU Tarbiyatul Athfal Kindergarten level. A total of 125 children received counselling and distribution of the drug albendazole. The result and conclusions obtained by administering worm medicine were appropriate because all children each received 1 tablet of albendazole.